UPAYA PENINGKATAN MINAT SISWA DAN SISWI SMAN 4 CILEGON (SURALAYA) DALAM MELANJUTKAN STUDI KE PERGURUAN TINGGI - Widiansyah, Subhan; Farhan, Muhammad; Mahardika, Chandra; Defita, Defita; Insam, Verosita; Maelawati, Intan Khoeroni; Meliana, Dina; Auli, Cikal Tazkia (Jurnal Pengabdian Dinamika, 2021)
Everyhigh schoolstudentinfact willbefaced with choicesinhis life, oneof whichiswhen they are presentedinthe futurebeforetheygraduatefromschool.Thechoicestheywillfindinclude,whethertheywillsetthemselvesuptocontinue theirstudiesinto theworldof lecturesor highereducation,take jobcourses,look for workor beunemployed.Likewise, thereare problemsinSuralaya Village,PulomerakDistrict,CilegonCity.AccordingtoMr. EmanSulaeman,especially inhighschoolfewhavethedesiretocontinue theireducationtotheworldoflecturesandonlyhavedirectorientation aftergraduatingfromcollege.ThisisourfoundationineducatingtheworkprogramoftheSocialization ofEntrance SelectionforUNTIRTAStateUniversities. Afterimplementing theUNTIRTAStateUniversityEntranceSelection SocializationprogramtheresultsobtainedintheinterestofstudentsandstudentsofSMAN4Cilegonincontinuingtheir studiestostateuniversitieswereintheNotTooHigh(Enough)category.